REGULATION OF MULTIDRUG TRANSPORTER LmrCD OF Lactococcus lactis - GHAISANI KOMARUDIN (NIM: 20511017); Pembimbing 1 : Dessy Natalia, Ph.D; Pembimbing 2: Pro, AMALINA
Lactococcus lactis is a Gram-positive, non-pathogenic and facultative anaerobic bacterium that can produce lactic acid from sugar fermentation. Several strains of Lactococcus lactis showed multidrug resistance phenotype when they are challenged with drugs. A multidrug transporter in Lactococcus lactis, LmrCD, is a heterodimeric ABC transporter constituted LmrC and LmrD. The expression of lmrCD is controlled by the transcription factor LmrR. This project focused on two topics namely determination binding affinity of the ligand riboflavin to LmrR and investigation on the lmrCD expression in the presence of substrate using Green Fluorescence Protein (GFP) fusions. Drug binding to LmrR was measured using fluorescence titration. The experiment was based on the change in fluorescence of Riboflavin (RBF) upon binding of this ligand to LmrR. For the reference, RBF was also titrated to the buffer without the protein. The excitation wavelength used was 435 nm and the emission wavelength was 523 nm. The results show that LmrR has a weak affinity to Riboflavin (Kd = 800 nM). Based on the differences of the LmrR Kd value, it suggests that there is a flexibility of LmrR as a multidrug induced transcription regulator. For the GFP fusion work, two constructs were created to fuse GFP with lmrD (translational fusion) and to fuse GFP behind a copy of the lmrCD promoter region (transcriptional fusion). The transcriptional GFP fusion and translational GFP fusion were constructed in E. coli and they were integrated to chromosomal DNA of Lactococcus lactis. The integration occurred via single cross over and selected via erythromycin resistance. To accomplish these gene fusions, the entire backbone of the integration vector must be excised. Afterwards, positive excisions are selected via negative selection based on 5-fluoroorotate sensitivity. At the excision step, two possibilities can occur, which are the excision of only the vector backbone and the fusion occurs or the vector and the gfpmut1 gene are both excised. For that reason, colony PCR is required to screen the GFP fusion. Positive colonies of the transcriptional GFP fusion and the translational GFP fusion were confirmed by colony PCR using GFP F1 primer and GFP R1 primer. For the toxic compound test, the fluorescence signal (excitation wavelength 480 nm, emission wavelength 510 nm) were measured every ten minutes for 4.5 hours. Monitoring of fluorescence signal was obtained from toxic compound test with pulse of drug. The fluorescence signal of Lactococcus lactis containing transcriptional GFP fusion and translational GFP fusion are slightly higher than the control strain.